CENTRAL MACULAR THICKNESS AFTER COMBINED THERAPY OF BEVACIZUMAB INTRAVITREAL INJECTION AND TOPICAL DICLOFENAC COMPARED WITH BEVACIZUMAB INTRAVITREAL INJECTION ALONE IN DIABETIC MACULAR EDEMA - Sandra, Melvina Nidya; Shabrina, Yumni; Widayanti, Tri Wahyu; Ekantini, Retno; Supartoto, Agus; Sasongko, Muhammad Bayu; Haryanto, Supanji (International Journal of Retina, 2021)
Introduction: To evaluate whether the combination of diclofenac eye drops and bevacizumab intravitreal injection would provide additional benefits over bevacizumab alone in the treatment of naïve diabetic macular edema (DME). Methods: A total of 43 patients were enrolled consecutively and randomized into two groups to receive combination treatment with intravitreal bevacizumab and topical diclofenac (group 1) or bevacizumab alone (group 2). Group 1 patients received single bevacizumab intravitreal injection and got self-administered diclofenac eye drop four times daily for one month. Group 2 patients received single bevacizumab intravitreal injection alone. Outcome data were obtained from patient visits at baseline and at 1 month after bevacizumab intravitreal injection. All patients underwent measurement of best corrected visual acuity (BCVA), a complete eye examination, and measurement of central macular thickness (CMT). Result: The mean reduction in CMT in the combination group was 130.42±32.57 µm (p<0.01), while in the bevacizumab alone group the reduction was 141.38±45.27 µm (p<0.01), there is no significant difference between the two groups (p=0.866). The mean improvement of BCVA was 0.32±0.10 log Mar in the combination group and 0.26±0.12 in group 2, there is no significant difference between the two groups (p=0.691). There was no adverse ocular event in the two groups. Conclusion: In patients with naïve DME, adding diclofenac eye drop as adjuvant of bevacizumab intravitreal injection are less likely to have a meaningful effect on reducing the central macular thickness. Keywords: Diabetic macular edema, NSAID, diclofenac, anti-VEGF, bevacizumab, central macular thickness